The Effect Of Compensation On Job Satisfaction Of Non-Civil Servant Employees At Haji Makassar Regional General Hospital - Sri Yuyun Afrianti; Mohammad Ardani Samad; Darmawati Junus; Widya Kirani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Human resources are a key factor in achieving quality hospital services. Employee job satisfaction is greatly influenced by the compensation received, such as salary, incentives, and allowances. At Haji Makassar Regional General Hospital, compensation for non-civil servant employees is one of the important factors affecting employee job satisfaction. To determine the effect of compensation, including salary, incentives, and allowances, on the job satisfaction of non-civil servant employees at Haji Makassar Regional General Hospital. This study used a quantitative approach with a cross-sectional design. The research subjects were non-civil servant employees using total sampling technique. Data collection was conducted by distributing questionnaires to employees. The data analysis techniques used were univariate and bivariate analyses.This study shows that there is an effect of compensation on salary indicator with value (p-value = 0.021<0.05), incentives with value (p-value = 0.003<0.05), allowances with value (p-value = 0.003<0.05) on job satisfaction of non-civil servant employees at Haji Makassar Regional General Hospital. There is an effect of salary, incentives, and allowances on job satisfaction of non-civil servant employees. It is expected that Haji Makassar Regional General Hospital maintains its compensation system.